Gwatemala – polityka wewnętrzna (od końca II wojny światowej do wojny domowej 1960 roku) - Romański, Mirosław (Acta Universitatis Lodziensis. Folia Historica, 2015)
The article presents mainly the little known form among the Polish researchers of general history, the issue of changes and processes of social-political nature in Guatemala arising during the period before ending the Second World War and the Civil War 1960. The author focused on discussion of the main aspects of internal and economic policy of that country, including the crucial role played by social tensions, political, social-economic changes, and also the coup. These factors had a determining role on the processes happening in the political sphere of Guatemala. The source basis of the article is information from the bulletin of the Ministry of Foreign Affairs of the People’s Republic of Poland and the archives of the Foreign Department of the Polish United Workers’ Party, which are in the Archive of New Files. The article is of the contributory nature, therefore the research within the subject matter is an open issue.